Cytotoxic alkaloids from the marine shellfish-associated fungus Aspergillus sp. XBB-4 induced by an amino acid-directed strategy. Issue 8 (27th January 2020) - Qiu, Yi; Guo, Qi; Ran, Yan-Qin; Lan, Wen-Jian; Lam, Chi-Keung; Feng, Gong-Kan; Deng, Rong; Zhu, Xiao-Feng; Li, Hou-Jin; Chen, Liu-Ping
Abstract : Cytotoxic alkaloids from marine fungus Aspergillus sp. XBB-4 induced by an amino acid-directed strategy. Abstract : Eight different culture media were used to culture shellfish Panopea abbreviate associated fungus Aspergillus sp. XBB-4. In a glucose-peptone-yeast (GPY) culture medium supplied with amino acids, this fungus can produce chemodiversity metabolites. Four new alkaloids including three β-carboline alkaloids, aspercarbolines A–C (1–3 ) and one piperazinedione, asperdione A (13 ) along with nine known compounds were isolated. The structures were elucidated mainly based on the NMR, MS, ECD and X-ray single-crystal diffraction data. The possible biosynthetic pathways of aspercarbolines A–C (1–3 ) were proposed. All compounds (1–13 ) were evaluated for their cytotoxicity against six cancer cell lines, including human nasopharyngeal carcinoma cell lines CNE1, CNE2, HONE1 and SUNE1, and human hepatocellular carcinoma cell lines hepG2 and QGY7701.